Reducing unnecessary preoperative testing through a comprehensive EMR based digital algorithmResearch in context - Stephen A. Esper; Jennifer Holder-Murray; Katie Meister; Hsing-Hua Sylvia Lin; Alison K. Bauer; Jamie Artman; Michael Garver; Amy Lukanski; Brian Scott Zuckerbraun; Oscar Marroquin; Aman Mahajan (EBioMedicine)
Summary: Background: We hypothesised that the implementation of an electronic medical record (EMR) embedded perioperative clinical decision support (CDS) application, Anesthesia Testing Guidelines (ATG), would result in at least a 10% reduction of unnecessary perioperative testing in patients undergoing elective surgeries. Methods: The development and implementation of ATG occurred in several phases: 1) team development, 2) development of an embedded EMR application, 3) creation of ATG training and education toolkit, and 4) implementation involving promoting ATG through training and education, addressing challenges, and monitoring compliance. The proportions of patients with any overutilisation across 19 perioperative tests were compared between the baseline cohort and the ATG implementation cohort. Findings: The overutilisation of perioperative tests was observed in 77.6% of the baseline cohort (n = 59,799) and 68.1% in the ATG cohort (n = 132,131), with a significant 12.2% reduction over two years of implementation (p < 0.0001). The two tests with the greatest amount of associated cost were reduced by 46% for chest X-rays and 39% for complete metabolic panels. The health system was able to reduce overall costs by 22% from baseline.Interrupted time series analysis estimated an immediate 7.5% decrease in monthly overutilisation when ATG initially launched, and it continued to decrease by 0.24% per month. Interpretation: Our findings suggest CDS ATG is a successful tactic to reduce unnecessary preoperative testing while maintaining quality of care and improving cost avoidance. This type of CDS implementation approach transforms organisational behaviour and medical practices to follow defined guidelines, thereby improving the value of care. Funding: CDS ATG was supported by UPMC Department of Anesthesiology and Perioperative Medicine and UPMC Department of Finance.